Change Management Strategies in Improving Organizational Resilience: An Approach Based on Innovation, Digitalization, and Adaptive Leadership - Dian Arlupi Utami; Yesa Cahayaning Ramadhani (PT. Anagata Sembagi Education, 2025)
Changes in a dynamic business environment require organizations to develop effective change management strategies to improve organizational resilience. This research discusses change management strategies in improving organizational resilience through innovation-based approaches, digitalization, and adaptive leadership. This research uses a qualitative approach with a case study design to analyze change management strategies in improving organizational resilience through innovation, digitalization, and adaptive leadership. The results showed that change management strategies based on innovation, digitalization, and adaptive leadership have a significant role in improving organizational resilience. Innovation allows organizations to stay relevant by creating new solutions in the face of evolving challenges. Digitalization plays a role in improving operational efficiency, accelerating decision-making, and opening up new opportunities through the use of technology. Meanwhile, adaptive leadership is a key factor in directing change with flexibility, building a culture that is responsive to external dynamics, and empowering human resources to be more responsive to change. The results of this study provide insights for organizational leaders in designing effective change management strategies to achieve resilience and sustainable growth.